(untitled) (Res Medica, 2014)
Infectious mononucleosis has long been an enigma to epidemiologists. The absence of a recognised causal agent or a specific diagnostic test has thrown confusion on such basic issues as the definition of the disease. Until very recently the diagnosis has had to be based on a triad consisting of characteristic signs and symptoms, an absolute increase in atypical mononuclear cells, and a positive heterophile aggultination (Paul Bunnell test) test. Unfortunately each of these criteria is subject to variation in interpretation while the rigid application of the three allows no margin for the diagnosis of subclinical or atypical disease. Within these limits of diagnosis, work on the epidemiology of the disease has produced very few concrete results. While there is no doubt that infectious mononucleosis has a peak incidence in young adults and is relatively uncommon in childhood and older age groups, the evidence concerning infectivity, incubation period and methods of transmission has been circumstantial and often based on a small number of observations. Conclusions drawn from such work suggests that although the disease occasionally develops in contacts it is not highly contagious, and there remains doubt as to whether epidemics of the classical disease have ever occurred. Estimations of the incubation period range between very wide limits, and although there is some evidence that the causal agent is transmitted in saliva (hence the term "kissing disease”) the method of natural transmission is still unproven. Many of these problems of the behaviour of infectious mononucleosis could be solved if a specific causal agent could be recognised and during the last six years the accumulation of evidence implicating the EB virus has caused considerable interest amongst epidemiologists.